2022
DOI: 10.1002/ame2.12250
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of different outcomes for tumor growth studies with animal models

Abstract: The consistency of reporting results for patient‐derived xenograft (PDX) studies is an area of concern. The PDX method commonly starts by implanting a derivative of a human tumor into a mouse, then comparing the tumor growth under different treatment conditions. Currently, a wide array of statistical methods (e.g., t‐test, regression, chi‐squared test) are used to analyze these data, which ultimately depend on the outcome chosen (e.g., tumor volume, relative growth, categorical growth). In this simulation stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The fixed effect of BH treatment was used to determine significance. Furthermore, to summarize the logistic average tumor growth curves with a single parameter, we calculated the AUC from day 14 to 35 for the averaged curves using the trapezoid rule 39 …”
Section: Methodsmentioning
confidence: 99%
“…The fixed effect of BH treatment was used to determine significance. Furthermore, to summarize the logistic average tumor growth curves with a single parameter, we calculated the AUC from day 14 to 35 for the averaged curves using the trapezoid rule 39 …”
Section: Methodsmentioning
confidence: 99%
“…The biological interaction between TME and PMN is increasingly important in tumor progression. Providing an animal model for the PMN is crucial for research and prediction 91,92 . Using liquid biopsy technology to detect the factors in PMN, exosomes, and CTCs as markers for early diagnosis and prediction of cancer is of great significance.…”
Section: Significance Of the Pmn For Tumor Metastasis Interventionmentioning
confidence: 99%
“…Providing an animal model for the PMN is crucial for research and prediction. 91 , 92 Using liquid biopsy technology to detect the factors in PMN, exosomes, and CTCs as markers for early diagnosis and prediction of cancer is of great significance. Some studies have confirmed that the expression of Tenascin‐C in regional lymph nodes may be a good predictor of bladder cancer metastasis, providing an important target for early metastasis intervention and treatment.…”
Section: Significance Of the Pmn For Tumor Metastasis Interventionmentioning
confidence: 99%